2011
DOI: 10.1002/jmri.22820
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of lipid composition of dissected sentinel lymph nodes of breast cancer patients by 7T proton MR spectroscopy

Abstract: Purpose: To determine lipid composition of excised healthy and metastatic sentinel lymph nodes of breast cancer patients, as lipids are a potential discriminatory marker for malignancy. Materials and Methods:Ten breast cancer patients undergoing surgical nodal staging were included. Results: In all, 6/32 (19%) of the excised nodes contained metastases. The ratios of the lipid resonances 5.4-5.2, 4.3-4.1, 2.8, 2.3-2.0, 1.6-1.3, 0.9 ppm between metastatic vs. benign were 0.3, 1.2, 0.2, 0.2, 1.2, and 0.9, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…PROTON MAGNETIC RESONANCE SPECTROSCOPY (MRS) has been used to assess fat unsaturation levels in a number of diseases in vivo . Adipose tissue, including that of bone marrow, in vivo is composed of ≈28% saturated (primarily palmitic acid), ≈51% monounsaturated (primarily oleic acid), ≈14% di‐unsaturated (primarily linoleic acid), and ≈1% tri‐unsaturated fatty acids .…”
mentioning
confidence: 99%
“…PROTON MAGNETIC RESONANCE SPECTROSCOPY (MRS) has been used to assess fat unsaturation levels in a number of diseases in vivo . Adipose tissue, including that of bone marrow, in vivo is composed of ≈28% saturated (primarily palmitic acid), ≈51% monounsaturated (primarily oleic acid), ≈14% di‐unsaturated (primarily linoleic acid), and ≈1% tri‐unsaturated fatty acids .…”
mentioning
confidence: 99%
“…PROTON MAGNETIC RESONANCE SPECTROSCOPY (MRS) measurements of lipids have been shown to be relevant in the study of a number of diseases (1–10). In particular, the degree of unsaturation may help identify patients who are at risk of such diseases, and may potentially be useful as a biomarker for early diagnosis, for detecting axillary breast cancer metastases, and for monitoring response to therapy (11–16). The levels of unsaturated and polyunsaturated fatty acids composing a lipid can be deduced from the MRS olefinic (≈5.4 ppm) and diallylic (≈2.8 ppm) resonances, respectively.…”
mentioning
confidence: 99%
“…NMR performed in lymph nodes has a sensitivity and specificity of 80 and 91%, respectively; however, accuracy had been shown to decrease when used for patients who have undergone neoadjuvant chemotherapy . In addition, 7‐T proton magnetic resonance spectroscopic images (MRSI) have been used ex vivo to identify lipid changes in metastatic lymph nodes compared to benign tissue, and it has been suggested that the technique could be used in vivo . In the future, spectroscopy may compliment conventional histology and reduce the burden on pathologists by offering an objective, quick and cost‐effective method for intraoperative metastasis diagnosis.…”
Section: Intraoperative Approachesmentioning
confidence: 99%
“…100 In addition, 7-T proton magnetic resonance spectroscopic images (MRSI) have been used ex vivo to identify lipid changes in metastatic lymph nodes compared to benign tissue, and it has been suggested that the technique could be used in vivo. 101 In the future, spectroscopy may compliment conventional histology and reduce the burden on pathologists by offering an objective, quick and cost-effective method for intraoperative metastasis diagnosis. However, before their widespread intraoperative use, diagnostic algorithms, data processing and spectral databases must be significantly improved.…”
Section: Spectroscopic and Tomographic Approachesmentioning
confidence: 99%